The CaaX Proteases, Afc1p and Rce1p, Have Overlapping but Distinct Substrate Specificities - Trueblood, Cynthia Evans (American Society for Microbiology, 2000)
Many proteins that contain a carboxyl-terminal CaaX sequence motif, including Ras and yeast a-factor, undergo a series of sequential posttranslational processing steps. Following the initial prenylation of the cysteine, the three C-terminal amino acids are proteolytically removed, and the newly formed prenylcysteine is carboxymethylated. The specific amino acids that comprise the CaaX sequence influence whether the protein can be prenylated and proteolyzed. In this study, we evaluated processing of a-factor variants with all possible single amino acid substitutions at either the a(1), the a(2), or the X position of the a-factor Ca(1)a(2)X sequence, CVIA. The substrate specificity of the two known yeast CaaX proteases, Afc1p and Rce1p, was investigated in vivo. Both Afc1p and Rce1p were able to proteolyze a-factor with A, V, L, I, C, or M at the a(1) position, V, L, I, C, or M at the a(2) position, or any amino acid at the X position that was acceptable for prenylation of the cysteine. Eight additional a-factor variants with a(1) substitutions were proteolyzed by Rce1p but not by Afc1p. In contrast, Afc1p was able to proteolyze additional a-factor variants that Rce1p may not be able to proteolyze. In vitro assays indicated that farnesylation was compromised or undetectable for 11 a-factor variants that produced no detectable halo in the wild-type AFC1 RCE1 strain. The isolation of mutations in RCE1 that improved proteolysis of a-factor-CAMQ, indicated that amino acid substitutions E139K, F189L, and Q201R in Rce1p affected its substrate specificity.